2003
DOI: 10.4049/jimmunol.171.2.938
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF Restores Innate, But Not Adaptive, Immune Responses in Glucocorticoid-Immunosuppressed Human Blood In Vitro

Abstract: Infection remains the major complication of immunosuppressive therapy in organ transplantation. Therefore, reconstitution of the innate immunity against infections, without activation of the adaptive immune responses, to prevent graft rejection is a clinically desirable status in transplant recipients. We found that GM-CSF restored TNF mRNA and protein expression without inducing IL-2 production and T cell proliferation in glucocorticoid-immunosuppressed blood from either healthy donors or liver transplant pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 67 publications
2
16
0
Order By: Relevance
“…These findings suggested that such differentiated M could evoke abnormal inflammation because they produced large amounts of TNF-␣ and MMP-9, even, without TNF-priming. However, GM-CSF is known to induce M, termed proinflammatory type 1 M (51), which have important roles in defense against infection (52), but a limited role in adaptive immunity (53). These data are consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…These findings suggested that such differentiated M could evoke abnormal inflammation because they produced large amounts of TNF-␣ and MMP-9, even, without TNF-priming. However, GM-CSF is known to induce M, termed proinflammatory type 1 M (51), which have important roles in defense against infection (52), but a limited role in adaptive immunity (53). These data are consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…The contrasting effects of GM-CSF and DEX may also occur via the amount of expression of dectin-1, the major macrophage receptor for b-glucans [23]. Support for our model of GM-CSF-mediated resistance to DEX-induced inhibition of conidia-stimulated NF-kB activation was recently reported in a study in which LPS was used instead of conidia [24]. In that study, GM-CSF restored expression of mRNA for TNF-a that was suppressed by DEX in human peripheral blood mononuclear cells in response to LPS.…”
Section: Discussionsupporting
confidence: 53%
“…We postulated that this was due to low levels of receptors for GM-CSF in lymphocytes. In support of this concept, Xu et al showed that GM-CSF neither caused graft rejection in DEXtreated mouse graft recipients nor reversed the DEX-suppressed proliferative response of lymphocytes [24]. However, GM-CSF reversed DEX immunosuppression in a model of lethal Salmonella typhimurium infection in which GM-CSF significantly increased survival [24].…”
Section: Discussionmentioning
confidence: 81%
“…Short-term treatment with GM-CSF has been shown to counteract impaired innate immune function due to a variety of insults. Ex vivo exposure to GM-CSF has restored function in monocytes harvested from humans with septic shock (36) or from immunosuppressed liver transplant recipients (37). In a rat model of hemorrhagic shock, GM-CSF treatment in vivo has corrected tissue macrophage dysfunction (17).…”
Section: Discussionmentioning
confidence: 99%